Influence of ultrasonic tool oscillation during drilling of fused silica - Henkel, Sebastian; Binder, Marcel; Knauf, Monique; Bliedtner, Jens; Rädlein, Edda (Advanced Optical Technologies, 2024)
The creation of holes in hard-brittle materials is highly relevant for various applications. The often-necessary high aspect ratios of the drill holes pose a particular challenge, with drill diameters of a few millimeters and drill lengths of up to several hundred millimeters. This requires the application of suitable tools with a high aspect ratio and sufficient stability. In particular the drilling process itself must be thoroughly understood and optimized in order to produce deep holes without component and tool defects while maintaining the required dimensional and positional accuracy. This paper presents investigations on the influence of an ultrasonic tool oscillation for drilling high aspect ratio holes. Two kinematic approaches, deep drilling and helical drilling, are examined with focus on the achievable dimensional accuracy of the holes and the roughness of the inner walls of the bore. It is found, that adding a longitudinal high frequency tool oscillation enables a considerable reduction in dimensional deviations of 91% for helical drilling.